2010
DOI: 10.1159/000253855
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Adalimumab in a Multicenter Swiss Cohort of Patients with Crohn’s Disease

Abstract: Background: Controlled clinical trials have demonstrated the efficacy and safety of adalimumab in patients with moderate-to-severe Crohn’s disease (CD), but there is, however, only limited long-term experience with adalimumab in daily practice. Aim: To assess the long-term effectiveness and safety of adalimumab in a multicenter cohort of practice-based patients with moderate-to-severe CD. Methods: We retrospectively reviewed the charts of CD patients who received adalimumab over a 3-year period. Disease severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The literature search revealed 797 references in Pubmed and 1067 in Embase; however, some references were excluded, among other reasons, for duplication and non‐availability of data on the effectiveness of the second anti‐TNF . Finally, only 46 studies met the inclusion criteria and were included . Of these, 37 focused on CD (Tables S1 and S2), 8 on UC, and 1 on pouchitis (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search revealed 797 references in Pubmed and 1067 in Embase; however, some references were excluded, among other reasons, for duplication and non‐availability of data on the effectiveness of the second anti‐TNF . Finally, only 46 studies met the inclusion criteria and were included . Of these, 37 focused on CD (Tables S1 and S2), 8 on UC, and 1 on pouchitis (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Data from adalimumab are limited; the only study so far showed a non-significant but lower response in smokers compared with non-smokers at 4–6 weeks 54. However, there have been concerns over the safety and efficacy of the use of infliximab in smokers.…”
Section: Effect Of Smoking On Drug Responsesmentioning
confidence: 99%
“…Similar results have been demonstrated for certolizumab pegol. 17 However, these findings have been disputed by other open label cohort studies that have not demonstrated the same effect of early anti-TNF therapy on clinical response, 18 remission, 19 or dose escalation for secondary loss of response. 20 Furthermore, previous studies have not evaluated whether earlier initiation of anti-TNF therapy alters the long-term surgical risk in CD.…”
mentioning
confidence: 99%